2011
DOI: 10.2139/ssrn.1785845
|View full text |Cite
|
Sign up to set email alerts
|

Tick Size Regulation, Intermarket Competition and Sub-Penny Trading

Abstract: The minimum price variation, or tick size, is at the center of the current regulatory debate as it a¤ects competition for liquidity provision in limit order books. A reduction in the tick size is …rstly shown to have a detrimental e¤ect on the quality of illiquid stocks as it worsens both spread and depth; but it bene…ts liquid stocks as it reduces inside spread and increases market depth. Then we build a dual-market model and examine how competition between two public limit order books (PLB) ends up with liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Most models of limit order books have pure private values and do not have asymmetric information regarding the asset value. Papers taking this approach include Parlour (1998), Foucault (1999, Foucault, Kadan, and Kandel (2005), Goettler, Parlour, and Rajan (2005), Rosu (2009), andButi, Rindi, Wen, andWerner (2011), among others. Chakravarty and Holden (1995), Kaniel and Liu (2006), and Goettler, Parlour, and Rajan (2009) allow informed traders, but incorporating a dark pool into their models is far from trivial.…”
Section: Markets and Tradersmentioning
confidence: 99%
“…Most models of limit order books have pure private values and do not have asymmetric information regarding the asset value. Papers taking this approach include Parlour (1998), Foucault (1999, Foucault, Kadan, and Kandel (2005), Goettler, Parlour, and Rajan (2005), Rosu (2009), andButi, Rindi, Wen, andWerner (2011), among others. Chakravarty and Holden (1995), Kaniel and Liu (2006), and Goettler, Parlour, and Rajan (2009) allow informed traders, but incorporating a dark pool into their models is far from trivial.…”
Section: Markets and Tradersmentioning
confidence: 99%
“…This type of transactional control coming out of the private sector of the market has often been sighted as a cause of increased spread in prices and increased market volatility (Degryse 2011, Jiang 2011, Weaver 2011, Comerton-Forde 2012 discussed the market share held in the private sector of the market as being indicative of volatility levels). Others have found that the market shares associated with a dark or private sector behaving in this manner may not lead to increasing volatility (Buti 2011, Ye 2011. The previous studies relating the behavior of private sector participants and the volatility of the market as a whole have generally assumed that the private sector of the market reports its volume and price informational parameters to the public real time.…”
Section: Case 1: Traditional Public Exchange Transactionmentioning
confidence: 99%